Occlusive Coronary Thrombosis and Oral Anticoagulants - Barrillon, A.; Kusmierek, J.; Gerbaux, A. (Thrombosis and Haemostasis, 1979)
The results of post-mortem examination in 173 patients followed over an average period of five and a half years after their initial myocardial infarction are described. These 173 patients were divided into four groups according to whether or not they had received an oral anticoagulant and if so how adequately. An index of coronary and myocardial lesions was established for each heart. Recent occlusive coronary thromboses were four times less frequent in the group of patients who had received adequate anticoagulant therapy than in the other three groups of patients (p˂0,001). There was no significant difference between the inadequately treated groups and the untreated group. The recurrences of myocardial infarction were associated in 90 per cent of the cases with a recent occlusive thrombosis in the corresponding coronary artery and were found four times less frequently in the group subjected to effective long-term anticoagulant therapy (p˂0,001).